Ablating the Transporter Sodium‐Dependent Dicarboxylate Transporter 3 Prevents Leukodystrophy in Canavan Disease Mice. Issue 5 (24th September 2021) - Wang, Yan; Hull, Vanessa; Sternbach, Sarah; Popovich, Brad; Burns, Travis; McDonough, Jennifer; Guo, Fuzheng; Pleasure, David
Abstract : Canavan disease is caused by ASPA mutations that diminish brain aspartoacylase activity, and it is characterized by excessive brain storage of the aspartoacylase substrate, N ‐acetyl‐l ‐aspartate (NAA), and by astroglial and intramyelinic vacuolation. Astroglia and the arachnoid mater express sodium‐dependent dicarboxylate transporter (NaDC3), encoded by SLC13A3, a sodium‐coupled transporter for NAA and other dicarboxylates. Constitutive Slc13a3 deletion in aspartoacylase‐deficient Canavan disease mice prevents brain NAA overaccumulation, ataxia, and brain vacuolation. ANN NEUROL 2021;90:845–850